Proses Pembuatan Roundown dan Que Card Event Darmo Car Free Day (CFD) Di TV9 Nusantara Surabaya - Lathifatun Nisa; Nashihin, Nashihin (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2023)
The Darmo Car Free Day (CFD) program is an event program that is held every Sunday by TV9 Nusantara. In realizing the program, the implementation of the program includes three production management processes, namely pre-production, production and post-production. Pre-production includes how to manage the program, starting from making concepts, arranging roundwon events, making queue cards, determining talent programs, arranging cameramen, to determining program speakers, as well as collaborating and looking for sponsors.